Snake and staff symbolism and healing - Francois P. Retief; Louise Cilliers (Acta Theologica)
Since time immemorial the snake has been venerated as an enigmatic creature with supernatural powers. As a snake and staff symbol it is also traditionally associated with the healing arts, either as the single-snake attribute of Asclepius, or as the doublesnake attribute of Hermes. In this article the mythological basis for this symbol is reviewed. The Asclepian emblem has been associated with health care since the 5th century BC when Asclepius became accepted by the Greeks as the god of healing. Whether he was also an historical figure as healer in earlier ages is less certain. The origin of the double-snake emblem is shrouded in the mists of antiquity. In classical times it became the herald’s wand (caduceus) of Hermes, messenger of the gods who guided departed souls to the Underworld, and was seen as the protector of travellers, shepherds and merchants. In the latter capacity Hermes also conveyed a negative connotation as protector of thieves. During the Middle Ages the caduceus entwined with the double-snake became a symbol of the healing sciences (pharmacy and alchemy in particular) and today, although mythologically incorrect, it is in common usage in the health care field.